Targeted Public Health Training for Neurosurgeons: An Essential Task for the Prioritization of Neurosurgery in the Evolving Global Health Landscape. Issue 1 (25th January 2023) - Rallo, Michael S.; Strong, Michael J.; Teton, Zoe E.; Murazsko, Karin; Nanda, Anil; Liau, Linda; Rosseau, Gail
Abstract : The gap between the tremendous burden of neurological disease requiring surgical management and the limited capacity for neurosurgical care has fueled the growth of the global neurosurgical movement. It is estimated that an additional 23 300 neurosurgeons are needed to meet the burden posed by essential cases across the globe. Initiatives to increase neurosurgical capacity through systems strengthening and workforce development are key elements in correcting this deficit. Building on the growing interest in global health among neurosurgical trainees, we propose the integration of targeted public health education into neurosurgical training, in both high-income countries and low- and middle-income countries. This effort will ensure that graduates possess the fundamental skillsets and experience necessary to participate in and lead capacity-building efforts in the developing countries. This additional public health training can also help neurosurgical residents to achieve the core competencies outlined by accreditation boards, such as the Accreditation Committee on Graduate Medical Education in the United States. In this narrative review, we describe the global burden of neurosurgical disease, establish the need and role for the global neurosurgeon, and discuss pathways for implementing targeted global public health education in the field of neurosurgery.